Origin and Pathways of Dissolved Organic Carbon in a Small Catchment in the Lena River Delta - Stolpmann, Lydia; Mollenhauer, Gesine; Morgenstern, Anne; Hammes, Jens S.; Boike, Julia; Overduin, Pier Paul; Grosse, Guido (Frontiers in Earth Science, 2022)
The Arctic is rich in aquatic systems and experiences rapid warming due to climate change. The accelerated warming causes permafrost thaw and the mobilization of organic carbon. When dissolved organic carbon is mobilized, this DOC can be transported to aquatic systems and degraded in the water bodies and further downstream. Here, we analyze the influence of different landscape components on DOC concentrations and export in a small (6.45 km2) stream catchment in the Lena River Delta. The catchment includes lakes and ponds, with the flow path from Pleistocene yedoma deposits across Holocene non-yedoma deposits to the river outlet. In addition to DOC concentrations, we use radiocarbon dating of DOC as well as stable oxygen and hydrogen isotopes (δ18O and δD) to assess the origin of DOC. We find significantly higher DOC concentrations in the Pleistocene yedoma area of the catchment compared to the Holocene non-yedoma area with medians of 5 and 4.5 mg L−1 (p < 0.05), respectively. When yedoma thaw streams with high DOC concentration reach a large yedoma thermokarst lake, we observe an abrupt decrease in DOC concentration, which we attribute to dilution and lake processes such as mineralization. The DOC ages in the large thermokarst lake (between 3,428 and 3,637 14C y BP) can be attributed to a mixing of mobilized old yedoma and Holocene carbon. Further downstream after the large thermokarst lake, we find progressively younger DOC ages in the stream water to its mouth, paired with decreasing DOC concentrations. This process could result from dilution with leaching water from Holocene deposits and/or emission of ancient yedoma carbon to the atmosphere. Our study shows that thermokarst lakes and ponds may act as DOC filters, predominantly by diluting incoming waters of higher DOC concentrations or by re-mineralizing DOC to CO2 and CH4. Nevertheless, our results also confirm that the small catchment still contributes DOC on the order of 1.2 kg km−2 per day from a permafrost landscape with ice-rich yedoma deposits to the Lena River.